Framework Development of Intelligence, Surveillance, and Reconnaissance (ISR) Based Geographic Information System for Common Operating Picture (COP) to Support Damai Cartenz Operation - Asyraf Atthariq Putra Gary (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Operation Damai Cartenz is a joint operation between the Indonesian National Police (POLRI) and the Indonesian National Armed Forces (TNI) in the Papua region to face security challenges in the region. The rugged terrain and complex operational environment in the Papua region are one of the challenges in carrying out this operation, so a strategy is needed to run it, one of which is by utilizing a Geographic Information System (GIS). The Geographic Information System (GIS) is one of the pieces of information that can assist officials in mapping areas. The application of GIS in operations can be further developed through the use of information resources owned by the Task Force. One of the things that can be done is by integrating Intelligence, Surveillance, and Reconnaissance (ISR) and Common Operating Picture (COP) capabilities in GIS. The main objective of this research is to be able to develop and offer a conceptual framework for integrating ISR and COP capabilities for GIS in supporting the Cartenz Peaceful Operation in the Papua region which includes explanations regarding requirements and addressing operational challenges through the implementation of effective integration of ISR and COP capabilities.